1991
DOI: 10.1165/ajrcmb/5.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of hsp70 Stress Proteins in Human Endothelial Cells Exposed to Heat Shock and Hydrogen Peroxide

Abstract: The potential role of oxidative stress conditions in the induction of heat shock proteins was studied in human umbilical vein endothelial cells. We compared the effects of temperature (43 to 45 degrees C), exposure to hydrogen peroxide (H2O2) and oxygen metabolites generated by the enzyme system hypoxanthine-xanthine oxidase (O2- plus H2O2), as well as exposure to 95% O2, on the expression of the major 70-kD heat shock proteins (hsp70). Northern blot analysis indicated that: (1) heat shock induced a rapid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 63 publications
2
30
0
Order By: Relevance
“…Expression of hsp68 was significantly stronger and faster induced by HS compared with OS as reported previously (34,52,53). In some previous studies no induction after OS was reported (9,54,55).…”
Section: Discussionsupporting
confidence: 87%
“…Expression of hsp68 was significantly stronger and faster induced by HS compared with OS as reported previously (34,52,53). In some previous studies no induction after OS was reported (9,54,55).…”
Section: Discussionsupporting
confidence: 87%
“…4A). Furthermore, Hsp70, which is highly induced by oxidative stress in human endothelial cells (24,35), was not induced by homocysteine. In contrast, Hsp70 was highly induced by hydrogen peroxide, and its induction was efficiently suppressed by pretreatment of cells with NAC (Fig.…”
Section: Cell Death Induced By Homocysteine Is Specific and Is Not Mementioning
confidence: 89%
“…HSPs are induced as an adaptive response on exposure to a variety of cellular injuries including oxidative damage. In particular, the cytosolic, inducible, 72 kDa HSP (Hsp70) is induced by oxidants both in vitro and in vivo (8)(9)(10), and its expression has been used as an indicative response to environmental stress and an interesting candidate as biomarkers of effect (11)(12)(13)(14). Optimal biomarkers would be biomarkers of exposure, which could provide the earliest, most upstream warning signs of environmental stress exposure.…”
mentioning
confidence: 99%